Reclaiming the 'competent' practitioner: furthering the case for the practically wise coach. Issue 1 (2nd January 2021) - Jones, Robyn L.; Hemmestad, Liv B.
ABSTRACT: The principal purpose of this paper is to further the case for phronesis as a progressive coaching concept. It is thus argued that coaching be considered (1) as a "geneology", (2) as contextualist in nature, (3) as being imbedded in the minutiae of action, and (4) as ethical practice. To these we add the notions of emergence and situational literacy. Although to a degree theory-led, we co-constructed the argument through recourse to an 18-month ethnographic study of the Norwegian national female handball team, and in particular the actions of head coach Marit Breivik during the period of investigation. What was embarked upon here was akin to a contested dialogue between phronetic theory and the available empirical data. In advocating the general case of coaching to be informed by phronetic principles, we reclaim the coach as a "competent" practitioner, a term involving emergent self-awareness and discernible judgement in relation to contextual goings-on.